Current trends in formulation and application of pharmaceutical preparations in therapy of depression in children and adults - Đuriš Jelena; Cvijić Sandra; Aleksić Ivana (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2017)
Depression is the most common mental disorder in the general population and often requires long-term administration of antidepressants. Development of the modified release antidepressant products has led to the lower incidence of the adverse effects and improvement in the adherence, and subsequently to better therapeutic outcomes. Modified release may involve delayed and/or prolonged release of antidepressants. There is an increasing number of marketed antidepressant products in the form of orally dispersible tablets, for the treatment of a particular group of patients with impaired swallowing. Pharmacotherapy of depression in children represents a great challenge due to insufficient data regarding efficacy and safety. Furthermore, in the market of Republic of Serbia, there are no antidepressant products in the age-appropriate dosage forms for pediatric patients. It is, therefore, of great importance to address the risks related to the application of the conventional dosage forms of marketed antidepressants (tablets, hard capsules) to children. Novel treatment options include development of carriers for targeted delivery of antidepressants in the central nervous system. Intranasal administration of antidepressants is particularly favored since it allows the delivery of active ingredients via olfactory and trigeminal nerves. Other transmucosal routes of administration, such as buccal or sublingual, can provide improved therapeutic outcomes, compared to the conventional oral administration, due to circumvention of the intense metabolism of the active ingredients and undesired gastrointestinal side effects.